2009
DOI: 10.1007/s00216-009-2934-2
|View full text |Cite
|
Sign up to set email alerts
|

Photonic sensor devices for explosive detection

Abstract: For the sensitive online and in situ detection of gaseous species, optical methods are ideally suited. In contrast to chemical analysis, no sample preparation is necessary and therefore spectroscopic methods should be favorable both in respect of a fast signal recovery and economically because no disposal is needed. However, spectroscopic methods are currently not widely used for security applications. We review photonic sensor devices for the detection of explosives in the gas phase as well as the condensed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Short stand-off detection (8 inches) of bulk TNT (1 mg mm −2 ) was obtained using an ultrasensitive microphone, and increased to 2.5 m using a 0.6 m diameter parabolic sound reflector [202,206]. The C-O stretch, centered near 8.3 μm, of the homemade explosive TATP was detected in the gas phase in the near field using QE-PAS [205,212]. Multivariate analysis has also been used in combination with IR (9-11 μm, 30-500 mW) scanning PAS in a cavity cell configuration to identify less than 100 μg DNT, TNT, Tetryl, RDX, HMX, PETN, and TATP [213].…”
Section: Photoacoustic Spectroscopymentioning
confidence: 99%
“…Short stand-off detection (8 inches) of bulk TNT (1 mg mm −2 ) was obtained using an ultrasensitive microphone, and increased to 2.5 m using a 0.6 m diameter parabolic sound reflector [202,206]. The C-O stretch, centered near 8.3 μm, of the homemade explosive TATP was detected in the gas phase in the near field using QE-PAS [205,212]. Multivariate analysis has also been used in combination with IR (9-11 μm, 30-500 mW) scanning PAS in a cavity cell configuration to identify less than 100 μg DNT, TNT, Tetryl, RDX, HMX, PETN, and TATP [213].…”
Section: Photoacoustic Spectroscopymentioning
confidence: 99%
“…The two CÀO stretch bands nearñ ¼ 1200 cm À1 can clearly be seen. Assuming the equilibrium concentration of $65 ppm for TATP in ambient air, a theoretical detection limit of 1 ppm TATP can be estimated with this set-up at ambient pressure and temperature conditions [69].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The detection of explosives and related compounds is an issue of major importance in different fields. Nearly all known analytical methods have already been investigated for their applicability to analyze explosives (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A review of the instrumentation used for trace detection of explosives was given by Moore in 2004 (1) and was supplemented with advances in 2007 (2).…”
mentioning
confidence: 99%
“…A review of the instrumentation used for trace detection of explosives was given by Moore in 2004 (1) and was supplemented with advances in 2007 (2). Some more recent reviews of the various analytical methods can be found in the literature (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In general, gas chromatography (GC) is the method of choice, while a range of different detectors can be coupled with this instrument.…”
mentioning
confidence: 99%